Odpowiedź:
[tex]Poziom\ \ B\\\\e)\\\\\frac{3x+2}{4}+5=\frac{2x+1}{3}\ \ |\cdot12\\\\3(3x+2)+60=4(2x+1)\\\\9x+6+60=8x+4\\\\9x+66=8x+4\\\\9x-8x=4-66\\\\x=-62\\\\\\f)\\\\\frac{x+2}{4}+1=\frac{x+6}{4}\ \ |\cdot4\\\\x+2+4=x+6\\\\x+6=x+6\\\\x-x=6-6\\\\0=0\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n\\\\\\g)\\\\\frac{x}{3}+2=7\ \ |\cdot3\\\\x+6=21\\\\x=21-6\\\\x=15[/tex]
[tex]Poziom\ \ C\\\\a)\\\\(x+3)(1-2x)+2x^2=0\\\\x-2x^2+3-6x+2x^2=0\\\\-5x+3=0\\\\-5x=-3\ \ |:(-5)\\\\x=\frac{3}{5}\\\\\\b)\\\\(x+4)(x-1)=x(x+2)+9x-1\\\\x^2-x+4x-4=x^2+2x+9x-1\\\\x^2+3x-4=x^2+11x-1\\\\x^2+3x-x^2-11x=-1+4\\\\-8x=3\ \ |:(-8)\\\\x=-\frac{3}{8}\\\\\\c)\\\\x^2-(x+3)(x-3)=9\\\\x^2-(x^2-9)=9\\\\x^2-x^2+9=9\\\\9=9\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n[/tex]